Wireless capacitive sensing system based on thermal drawing flexible fiber sensor - Cao, Zhipeng (Nanyang Technological University, 2024)
With the rapidly growing demand for health monitoring as well as spatial computing, the application of flexible fiber materials in this field is becoming increasingly important, boosting the need for fiber data collection and processing. We develop the devices for real-time wireless sensing of flexible fiber capacitance (FCWSS), which can monitor and transmit the changes in the relative value of fiber capacitance with Bluetooth. Using copper wire or liquid metal in the fiber connected to the capacitance monitoring channel we developed, we construct a monitoring channel that can reflect fiber deformation in real time. The development history of flexible intelligent sensing devices and the working principle of capacitance monitoring are introduced in this paper. And we show the design process of wireless sensing system in hardware, structure and embedded development, describing the process of thermally drawn fiber preparation and the testing process and milestones of the sensing system. FCWSS promotes sensing technology in motion recognition and health monitoring, paving new paths for innovative applications of smart devices.